Iron-isopods: new records and new species of terrestrial isopods (Isopoda, Oniscidea) from Brazilian Amazon iron ore caves - López-Orozco, Carlos Mario; Campos-Filho, Ivanklin Soares; Gallo, Jéssica S.; Gallão, Jonas E.; Carpio-Díaz, Yesenia M.; Borja-Arrieta, Ricardo; Bichuette, Maria Elina (European Journal of Taxonomy, 2024)
Abstract. Two new species of terrestrial isopods are described from iron ore caves in Brazil, within the Amazon biome, Circoniscus mendesi López-Orozco, Campos-Filho & Bichuette sp. nov. and C. xikrin López-Orozco, Campos-Filho & Carpio-Díaz sp. nov. (Scleropactidae). In addition, the knowledge of the distribution of Ctenorillo ferrarai Campos-Filho, Araujo & Taiti, 2014 (Armadillidae) is extended to Parauapebas, and Benthanoides tarzan Cardoso & Ferreira, 2023 to south area of the Campos Ferruginosos National Park, both in the State of Pará. Moreover, a distribution map and photographs of the species are given.